KRITERIA BIOGRAFI TOKOH YANG BERMUATAN TOLERANSI KEHIDUPAN BERAGAMA - Main Sufanti; Fitri Puji Rahmawati; Markhamah -; Nuraini Fatimah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The purpose of this study were: (1) describe the criteria biographical charged religious tolerance value and (2) biography that meet the criteria for. This research is descriptive qualitative research that is part of the research and development. Data in the form of information in the form of informant statements about the criteria biographical containing values religious tolerance and biographical that meet these criteria. The data was collected by questionnaire and interview from 13 informants consisting of high school teachers and lecturers in Surakarta PBSI FKIP UMS. The data is then codified, tabulated, and analyzed with a critical analysis techniques. Results of the analysis are presented with a formal presentation and tables. Presented the results of this study as follows. (1) There are 44 criteria which can be classified biographical be criteria based on figures and criteria based on the contents of the biography. Criteria based on figures include: based on the character, the existence, religiosity, services / her work, and expertise. Criteria based on biographical forms include: content biography, language, biography, biography and origin. (2) The informant proposed a 39 character name which is considered to have the values of religious tolerance that can be used as an educational resource religious tolerance. However, only 18 were able to biographical mentioned identasnya complete.Kata kunci: tolerance, religious life, biography, education model